2021
DOI: 10.1088/2515-7647/abda24
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast adiabatic frequency conversion

Abstract: Ultrafast adiabatic frequency conversion is a powerful method, capable of efficiently and coherently transfering ultrashort pulses between different spectral ranges, e.g. from near-infrared to mid-infrared, visible or ultra-violet. This is highly desirable in research fields that are currently limited by available ultrafast laser sources, e.g. attosecond science, strong-field physics, high-harmonic generation spectroscopy and multidimensional mid-infrared spectroscopy. Over the past decade, adiabatic frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…In the past two decades, several methods have been proposed for the creation of efficient, broadband and robust frequency conversion processes. Among them are the random designs [10], the multi-periodic phase-matching [11,12] and chirped designs [1,[13][14][15][16], which exhibit broadband conversion capabilities that were shown also to be suitable for ultrashort pulse conversion and manipulation. Yet, these methods fail to offer a robust, broadband and efficient conversion process while maintaining short nonlinear crystal length and low pump intensity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past two decades, several methods have been proposed for the creation of efficient, broadband and robust frequency conversion processes. Among them are the random designs [10], the multi-periodic phase-matching [11,12] and chirped designs [1,[13][14][15][16], which exhibit broadband conversion capabilities that were shown also to be suitable for ultrashort pulse conversion and manipulation. Yet, these methods fail to offer a robust, broadband and efficient conversion process while maintaining short nonlinear crystal length and low pump intensity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was shown that a nonlinear crystal based on a gradual adiabatic variation of the phase mismatch parameter exhibits an efficient conversion for ultra-broadband or tunable quasi-continuouswave (quasi-CW) signals. Moreover, the adiabatic conversion scheme was implemented for sum and difference frequency conversion of ultrashort pulses [13,15], taking it to an extreme generation of octave spanning single cycle mid-infrared pulses [17]. In addition, the adiabatic scheme was extended to cascaded processes and also for depleted nonlinear processes [15].…”
Section: Introductionmentioning
confidence: 99%